Dental materials guide - Phinney, Donna J; Halstead, Judy H (Clifton Park, NY : Delmar Cengage Learning, 2009)
"From amalgam to zinc oxide eugenol, the Dental Materials Guide provides a quick reference for the uses and properties of materials commonly found in dental practice. This essential resource can be used during clinicals and labs and is also a handy study tool for examinations."--BOOK JACKET
Keywords: Dental materials; Dental Materials